Perspective: The Alzheimer's Disease Neuroimaging Initiative and the role and contributions of the Private Partner Scientific Board (PPSB). Issue 7 (1st July 2015) - Liu, Enchi; Luthman, Johan; Cedarbaum, Jesse M.; Schmidt, Mark E.; Cole, Patricia E.; Hendrix, James; Carrillo, Maria C.; Jones‐Davis, Dorothy; Tarver, Erika; Novak, Gerald; De Santi, Susan; Soares, Holly D.; et al.
Abstract: The Alzheimer's Disease Neuroimaging Initiative (ADNI) Private Partner Scientific Board (PPSB) is comprised of representatives of private, for‐profit entities (including pharmaceutical, biotechnology, diagnostics, imaging companies, and imaging contract research organizations), and nonprofit organizations that provide financial and scientific support to ADNI through the Foundation for the National Institutes of Health. The PPSB serves as an independent, open, and precompetitive forum in which all private sector and not‐for‐profit partners in ADNI can collaborate, share information, and offer scientific and private‐sector perspectives and expertise on issues relating to the ADNI project. In this article, we review and highlight the role, activities, and contributions of the PPSB within the ADNI project, and provide a perspective on remaining unmet needs and future directions.